Digitalized Ship Maintenance Management System Website Application Innovation Strategy Using Design Thinking Method - Wicaksono, Bayu Mahardika; Pratiwi, Emmy; Wahyurini, Octaviyanti Dwi (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The purpose of the study is to explore the benefits of digitalization, specifically in the context of PT Biro Klasifikasi Indonesia's (PT. BKI) digital transformation efforts. The focus is on how digitalization can enhance operational efficiency, productivity, customer service, and global competitiveness in the maritime industry. Method: The research employs the design thinking method to identify and address customer needs and challenges. It highlights the development of the "Digitalized Ship Management Maintenance System" application, showcasing its role in simplifying ship maintenance processes. The study uses a customer-centric approach to determine modules that provide effective solutions to identified issues. Result: The Digitalized Ship Management Maintenance System application is designed to streamline ship maintenance for customers. Utilizing design thinking, the study identifies customer problems and develops modules to address them. The application offers direct integration with PT. BKI's survey status, strengthening its international classification standing. Additionally, it supports government data integration, ensuring safety and environmental protection in Indonesia's maritime areas. Implication: The implications of the study underscore the significance of digital transformation for companies in the maritime sector, particularly for PT. BKI. The "Go Global" and "Big Top 5 Asia" targets align with the broader benefits of digitalization, including enhanced operational efficiency, global market access, and improved customer service. The developed application serves as a tangible outcome of the digitalization process, contributing to PT. BKI's competitiveness and its role as a trusted classification body.